2012
DOI: 10.1016/j.virol.2011.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Inefficient splicing of segment 7 and 8 mRNAs is an inherent property of influenza virus A/Brevig Mission/1918/1 (H1N1) that causes elevated expression of NS1 protein

Abstract: Influenza A virus encodes two segments (7 and 8) that produce mRNAs that can be spliced. We have investigated if naturally occurring sequence polymorphisms in the influenza A virus family affects splicing of these viral mRNAs, as that could potentially alter the NS1/NS2- and/or M1/M2-protein ratios. We compared splicing efficiency of segment 7 and 8 mRNAs of A/Brevig Mission/1918/1 (H1N1) and A/Netherlands/178/95 (H3N2), as well as various H5N1 avian strains. Results revealed that both segment 7 and 8 mRNAs of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 55 publications
2
17
0
Order By: Relevance
“…The data obtained demonstrated that although the amount of NS2 produced by the NS2-shifted constructs was decreased by half compared to that produced by the parental NS gene segments (Fig. 6A, compare the amounts of NS2 displayed by the different constructs, and B, compare bars 1 and 2 with bars 5 and 6), the amount of NS2 should still be sufficient to ensure virus survival because similar ratios of NS2 to NS1 are known to be produced by some human influenza viruses (58). Furthermore, no substantial difference in NS2 synthesis between the shifted constructs was observed (Fig.…”
Section: Ns1 Sumoylation Affects Viral Growth In Ifn-competent and Ifmentioning
confidence: 95%
“…The data obtained demonstrated that although the amount of NS2 produced by the NS2-shifted constructs was decreased by half compared to that produced by the parental NS gene segments (Fig. 6A, compare the amounts of NS2 displayed by the different constructs, and B, compare bars 1 and 2 with bars 5 and 6), the amount of NS2 should still be sufficient to ensure virus survival because similar ratios of NS2 to NS1 are known to be produced by some human influenza viruses (58). Furthermore, no substantial difference in NS2 synthesis between the shifted constructs was observed (Fig.…”
Section: Ns1 Sumoylation Affects Viral Growth In Ifn-competent and Ifmentioning
confidence: 95%
“…Recent studies have hypothesized that the splicing efficiency of the M and NS segments of IAV could be a determinant in their ability to replicate or to adapt to a new host, denoting an important concern for pathogenicity (79, 96). Chua and colleagues have recently demonstrated that suboptimal splicing of the NS segment plays a role as a “molecular timer” that coordinates the timing of infection (79).…”
Section: Is Splicing a Key Determinant For Viral Replication Host Ramentioning
confidence: 99%
“…Chua and colleagues have recently demonstrated that suboptimal splicing of the NS segment plays a role as a “molecular timer” that coordinates the timing of infection (79). Moreover, results obtained by Backström Winquist and colleagues have shown that the splicing efficiency of M and NS mRNAs varies between different influenza viruses (96). For example, the NS segment from A/Brevig Mission/1919/1 (H1N1) has been shown to be inefficiently spliced compared to those of other influenza viruses, possibly due to the differential binding properties of cellular splicing factors (e.g., SR proteins), resulting in the production of higher levels of functional NS1.…”
Section: Is Splicing a Key Determinant For Viral Replication Host Ramentioning
confidence: 99%
See 1 more Smart Citation
“…The NS1 and NEP proteins play different roles during virus infection and regulation of splicing of mRNA to favour either NS1 or NEP could significantly affect virus replication efficiency. Indeed, it is suggested that inefficient splicing of NS mRNAs of the pandemic A/Brevig Mission/1918/1 (H1N1) virus resulted in higher levels of the NS1 protein, contributing to its pathogenic properties19. NEP is required for coordination of viral ribonucleoprotein (RNP) nuclear export in the later stage of infection and it is suggested that virus adapts to utilize a poor 5′-splice site to allow slow expression of NEP early in virus infection20.…”
mentioning
confidence: 99%